2015
DOI: 10.2134/jeq2014.12.0547
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Transport in a Soil-Based Wastewater Treatment System under Simulated Operational and Climate Change Conditions

Abstract: Bacteria removal efficiencies in a conventional soil-based wastewater treatment system (OWTS) have been modeled to elucidate the fate and transport of bacteria under environmental and operational conditions that might be expected under changing climatic conditions. The HYDRUS 2D/3D software was used to model the impact of changing precipitation patterns, bacteria concentrations, hydraulic loading rates (HLRs), and higher subsurface temperatures at different depths and soil textures. Modeled effects of bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 56 publications
(77 reference statements)
0
13
0
Order By: Relevance
“…coli in soil. Generally, bacterial pathogens in soil experience increased mortality with increased temperatures [18,34]. However, our results suggest that the combination of warmer and wetter soils may have enhanced the transport, survival and/or growth of FCB in all STA types.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…coli in soil. Generally, bacterial pathogens in soil experience increased mortality with increased temperatures [18,34]. However, our results suggest that the combination of warmer and wetter soils may have enhanced the transport, survival and/or growth of FCB in all STA types.…”
Section: Resultsmentioning
confidence: 70%
“…coli transport in the STA at 20°C and 23°C found greater attenuation at the higher temperature, but predicted lower E . coli removal under simulated increases in rainfall leading to wetter soils [34]. These two effects were not coupled in the model; since we observed lower FCB attenuation in our experiment, this would suggest that the degree of soil moisture plays a larger role in bacterial removal than temperature.…”
Section: Resultsmentioning
confidence: 85%
“…The heterogeneity of porous media can affect pathogen migration by altering the collision efficiencies and deposition capacities, because of the higher attachment at secondary minima at concave locations or detachment from primary minima at nanoscale convex asperities ( Shen et al, 2020 ). Fine-textured and poor-structured soils intercept bacteria through mechanical filtration for their small pore sizes and low hydraulic conductivity ( Morales et al, 2015 ). Accordingly, an increasing virus migration is observed with the standard deviations of hydraulic conductivity in heterogeneous aquifers in a migration model ( Torkzaban et al, 2019 ).…”
Section: Environmental Geochemical and Hydrological Variablesmentioning
confidence: 99%
“…Modeling was especially beneficial when more than one pathway was involved in F&T, as in the case of simultaneous transport of 1,3-dichloropropen in both liquid and gaseous phases (Wang et al, 2000). A modeling study with multiple scenarios was found to be a useful instrument to evaluate the effect of climate change on F&T in waste management systems (Morales et al, 2015). Kalin et al (2010) reported the first application of machine learning to estimate water quality across watersheds.…”
Section: Modeling In Fandt Researchmentioning
confidence: 99%